Microsoft Azure: Backup and Disaster Recovery. - Bennett, Sharon (linkedin.com, 2018)
Learn how to back up and restore servers, virtual machines, files and folders, workloads, and databases with Microsoft Azure services such as Azure Backup and Azure Site Recovery.